Cuantificación contractual de daños y perjuicios. ¿Existen límites en el Ecuador? (Tema Central) - Plascencia Morales, Iván Leandro (2025)
It is necessary to start from a clear idea: the law of torts in Ecuador has remained immobile for decades with respect to the continuous evolution that the rest of the countries in the world have maintained. Although there are several aspects of tort law that could be approached to analyze possible doctrinal and/or jurisprudential updates, this research focuses on analyzing the basis of civil law, the voluntariness and autonomy of the parties at the time of contractually determining the form and amount of compensation for penal clauses accumulated to damages. The modifications that our substantive civil law has undergone during the last century, they have not been transcendental or clarifying within the scope of the proposed analysis, on the contrary, they have left the door open to visualize the problem and the possible solutions from a broader perspective, that of contractual freedom as a pillar of civil law, for which a doctrinal and jurisprudential analysis will be made. Re potentiating the original ideas of our civil code, after analyzing whether there are normative, doctrinal and/or jurisprudential prohibitions to the definition and contractual quantification of damages, the conclusion is that we can execute it freely, as an efficient remedy for the creditor.